THE INFLUENCE OF ORGANIZATIONAL CULTURE, COMPETENCE ON PATIENT SAFETY WITH WORK DISCIPLINE AS INTERVENING VARIABLES IN RS. YPK MANDIRI - Kurniawati, Nina; Djamil, Masyhudzulhak; Badawi Saluy, Ahmad (Dinasti Publisher, 2021)
This study focused on the form and influence of the organization, the level of discipline and competence possessed by nursing staff and their influence on the level of patient safety at YPK Mandiri Hospital. In this study, the respondents who participated were 100 people who worked in the hospital YPK Mandiri. The research design was cross sectional using a quantitative approach. Data collection by distributing questionnaires to all hospital employees. Data analysis using Partial Least Square (PLS) is an alternative method of Structural Equation Modeling (SEM). The results showed that there was no influence between organizational culture and work discipline, competence had a positive effect on discipline, organizational culture did not have a positive effect on patient safety, competence had a negative influence on patient safety culture, work discipline had a positive effect on patient safety, work discipline could not mediate Positively the influence of organizational culture on patient safety culture, work discipline cannot positively mediate the influence of competence on patient safety culture.